Bhutan’s first library qualification, background and development / Sylvia Ransom - Ransom, Sylvia (2011)
During a six month contract with the Royal University of Bhutan, the author was required to develop the initial stages of a first library qualification to be offered in Bhutan. Questions raised by this project included: Is a first qualification in librarianship needed in Bhutan? What are the potential student numbers in such a program? What structure should such a program take? What guidance exists for developing diploma programs at the Royal University of Bhutan? Does the country contain the expertise to run the program? The author utilized situational analysis to gather data for the program, building on a number of existing but unpublished documents relating to training library staff in Bhutan. Using the guidelines in existence, and the knowledge gained from the situational knowledge, data was gathered to answer the research questions. A three year, part time Diploma of Library Management to be offered by mixed mode (distance education) was designed, and supporting documentation written. There is no doubt that appropriate, relevant library training is needed for library staff in Bhutan. It is less clear that the resources currently exist to fully develop and present an initial diploma level qualification.